A brief systematic review of the literature on the economic, social and environmental impacts of shale gas exploitation in the United Kingdom. (December 2020) - Álvarez-Ramos, Carolina; Diez-Suárez, Ana-María; de Simón-Martín, Miguel; González-Martínez, Alberto; Rosales-Asensio, Enrique
Abstract: Fracking is a technology used for the extraction of shale gas contained in rocks on the Earth's surface. The main characteristic of this method is that it consists of injecting pressurized water into the ground, thus creating a series of fractures through which the gas comes out to be collected later. Fracking has a number of both socio-economic and environmental implications that can be both beneficial (including increased energy security, economic growth, or reduced emissions of pollutants and climate change) and harmful (induced seismicity, increased global temperature, and potential greenhouse emissions if not properly implemented). The realization of a systematic review of the literature classifying the articles found according to the type of evidence they present; that it gathers all the impacts has allowed to group them and to give a general vision about the topic; that no articles have been found that have this same objective in the existing literature, thus contributing to the increase of the existing knowledge in this field. It is concluded that environmental risks, including those that could affect human health, should be integrated into the cost structure of fracking, as a risk premium or provision of funds to remedy possible negative effects.